OTOLARYNGOLOGIC MANIFESTATIONS OF GASTROESOPHAGEAL REFLUX DISEASE: Gastroesophageal Reflux Disease - Ansari, Noor Alam; Memon, Jan Muhammad; Naqvi, Qaisar Hussain (Pakistan Armed Forces Medical Journal, 2008)
Objective: To determine frequency of endoscopic oesophagitis in the patients who complain the chronic laryngopharyngeal disorders in the absence of typical gastroesophageal Reflux Disease (GERD) symptoms. Design: Descriptive study Place & Duration of the Study: The study was carried out in the department of E.N.T at Nawabshah Medical Centre, Nawabshah over the period of two years (2004 to 2006). Patients & Methods: One hundred patients of either sex and in the age group between 25-79 years with symptoms of chronic laryngopharyngeal disorders were selected for study. All patients had physical examination of upper aero digestive tract. Direct laryngoscopy was done to evaluate the status of larynx, however rigid esophagoscopy was done to evaluate the status of esophageal mucosa and biopsies from lower part of esophagus were taken in all patients. Results: Eighty percent of patients with symptoms of chronic laryrigopharyngitis were also suffering from microscopic Oesophagitis. Among the 80% patients 87.5% were having non-erosive oesophagitis while 12.5% were having erosive oesophagitis. Conclusion: In significant number of patients with chronic upper respiratory symptoms resistant to the treatment, there was co existing gastroesophageal disease which could be the cause of the symptoms.